KONSTRUKSI DI ATAS TIMBUNAN SEBAGAI ALTERNATIF SALURAN SEKUNDER SUKAJAYA (BS.1) DAERAH IRIGASI WAY PENGUBUAN - Kartini Susilowati; Susetyo Hartanto (UNIVERSITAS LAMPUNG, 2009)
Sukajaya Secondary Channel of Way Pengubuan Irrigation Area has influence to irrigationschedule of paddy rice of service area. Sukajaya Secondary Channel has been designed by siphonconstruction. This construsction has been more than 30 years old since finished in 1979.Performance of the siphon deteriorated. With more than 300m length, it caused severalconsequences, for example sedimentation along siphon, leaking especially at the segment joint.From 5,000Ha potential servicing area reduced to 3,500.75 functional area. The aim of thisresearch was to give alternative design, namely: (1) sediment washed; (2) rehabilitation ofsegment joint; (3) to build new secondary channel by gutter construction; and (4) to build newsecondary channel by landfill. From the economic engineering point of view, new secondarychannel by landfill was the optimal option.